Exploring an innovative decellularization protocol for porcine nerve grafts: a translational approach to peripheral nerve repair - Muratori, Luisa; Crosio, Alessandro; Ronchi, Giulia; Molinaro, Debora; Tos, Pierluigi; Lovati, Arianna B.; Raimondo, Stefania (Frontiers in Neuroanatomy, 2024)
Peripheral nerves are frequently affected by lesions caused by traumatic or iatrogenic damages, resulting in loss of motor and sensory function, crucial in orthopaedic outcomes and with a significant impact on patients' quality of life. Many strategies have been proposed over years to repair nerve injuries with substance loss, to achieve musculoskeletal reinnervation and functional recovery. Allograft have been tested as an alternative to the gold standard, the autograft technique, but nerves from donors frequently cause immunogenic response. For this reason, several studies are focusing to find the best way to decellularize nerves preserving either the extracellular matrix, either the basal lamina, as the key elements used by Schwann cells and axons during the regenerative process. This study focuses on a novel decellularization protocol for porcine nerves, aimed at reducing immunogenicity while preserving essential elements like the extracellular matrix and basal lamina, vital for nerve regeneration. The idea of using a porcine nerve graft arises from a translational perspective. This approach offers a promising direction in the orthopaedic field for nerve repair, especially in severe cases where conventional methods are limited. The first aim of the present study was to test the efficacy of a decellularization method in order to evaluate its possible application to create efficient nerve grafts. The second aim was to evaluate the ability of the decellularized porcine nerve graft to repair median nerve lesions in rats. To investigate the efficacy of the decellularization protocol to remove immunogenic cellular components of the nerve tissue and to preserve the basal lamina and extracellular matrix, morphological analysis was performed through Masson’s Trichrome staining, immunofluorescence, high resolution light microscopy and transmission electron microscopy. Morphological analysis was also used to study the ability of the porcine decellularized graft to support the nerve regeneration. Four weeks after injury, regenerating fibers colonized the graft suggesting a promising use to repair severe nerve lesions.